Approaches to behavior and classroom management integrating discipline and care - Scarlett, W. George; Ponte, Iris Chin.; Singh, Jay P.; Sage eBooks (London : SAGE, 2009)
'Approaches to Behaviour and Classroom Management' focuses on teaching readers how to use a variety of approaches in behaviour and classroom management in order to make good decisions when faced with the challenge of creating positive classroom communities.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Classroom management; Behavioral assessment; Electronic books